PKM Permodelan Ekonomi Menggunakan Aplikasi System Dynamic - Samsir, Andi; Irwandi, Irwandi; Alam, Syamsu; Jamil, Muh.; Regina, Regina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
The partner of this Community Partnership Program (PKM) is LP2M Cokroaminoto University Makassar, South Sulawesi. Initial observations found various problems, namely: (1) not understanding panel data modeling with processing techniques in inputting data into the System Dynamic program which focuses on econometric analysis contained in panel data, (2) not knowing how to interpret or read panel data output. The solution to the problems found was given training with the target participants being students and lecturers of Cokroaminoto University Makassar. The number of participants who participated in this activity was 15 participants. The method approach used in solving existing problems is through lectures, demonstrations, discussions, questions and answers, and partner assistance. The results achieved are (1) partners have knowledge in economic modeling using the System Dynamic application, (2) partners have skills in operating the System Dynamic application, (3) partners have alternative econometric applications for data processing and economic data analysis. The success indicators of this activity can be seen from the participants' increased understanding of economic modeling with the System Dynamic application. Keywords: Economic Modeling; System Dynamic; Data Panel.